Peran Instansi Pemerintah dalam Mengatasi Perbuatan Gangguan Fungsi Jalan di Kota Pekanbaru - Rahayu, Sri; Rafi, Mhd. (PUBLICNESS: Journal of Public Administration Studies, 2024)
This research was conducted in Pekanbaru City with the aim of finding out more about the role of government agencies in overcoming acts of road dysfunction and to find out the obstacles that exist in overcoming acts of road dysfunction. The types and sources of data in this research are primary and secondary data. This research is descriptive qualitative, namely an analysis that provides a detailed picture based on observations, interview results, and also documentation. The results of this research show that the role of government agencies in overcoming road disruption in Pekanbaru City is seen from indicators ranging from policy planners, implementers. policies, and policy supervisors are said to play quite a role but there is still a need for improvement in terms of order and supervision. The low level of legal awareness, and supervision which is only carried out as a formality, as well as a lack of firmness in providing sanctions are the reasons why acts of disruption of road function are still not optimally resolved as expected.